2022
DOI: 10.1128/aem.01285-22
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Inferring Symbiont Function: Paraburkholderia Symbiont Dynamics in Social Amoeba Populations and Their Impacts on the Amoeba Microbiota

Abstract: The functions of symbionts in natural populations can be difficult to completely discern. The three Paraburkholderia bacterial farming symbionts of the social amoeba Dictyostelium discoideum have been shown in the laboratory environment to allow the amoebas to carry, rather than fully digest, food bacteria.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…First, our samples were not replicated over time, so our results do not capture the variation in Paraburkholderia symbiosis over time. This may be an important factor as other soil sampling studies have found that symbiosis with Paraburkholderia may vary over time in some locations ( DuBose et al, 2022 ). Second, our soil and climate measures do not capture within site heterogeneity that is important in many microbial systems ( Nannipieri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…First, our samples were not replicated over time, so our results do not capture the variation in Paraburkholderia symbiosis over time. This may be an important factor as other soil sampling studies have found that symbiosis with Paraburkholderia may vary over time in some locations ( DuBose et al, 2022 ). Second, our soil and climate measures do not capture within site heterogeneity that is important in many microbial systems ( Nannipieri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Environmental sampling has found that Paraburkholderia prevalence is about 25% of sampled hosts but varies by sampling location ( Haselkorn et al, 2019 ) and over time ( DuBose et al, 2022 ). Obligate endosymbionts are found in about 40% of sampled hosts ( Haselkorn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our post-hoc hypothesis for the lack of defense mechanisms in hosts of P. bonniea is related to the ecology of both host and symbiont. P. bonniea is the rarest of Paraburkholderia symbionts of D. discoideum (Haselkorn et al 2019; DuBose et al 2022) and it also appears to be the symbiont species that is least detrimental to host fitness on average (Miller et al 2020). Rare encounters between new hosts and P. bonniea may not have a significant impact on D. discoideum populations, particularly if D. discoideum itself is sparsely distributed across soil landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…These pieces of evidence indicate that P. agricolaris may be a generalist symbiont of social amoebas, and P. agricolaris infection from the environment and horizontal infection between amoebas may be common. The rarer P. bonniea and P. hayleyella are still elusive in terms of their natural host ranges (DuBose et al 2022). But given their relative scarcity and difference in genome size, we predict that both reduced-genome species are more likely to be specialists of D. discoideum .…”
Section: Discussionmentioning
confidence: 99%
“…Among a few studies, it is suggested that the endosymbionts provide benefits to their host Acanthamoeba by enhancing Acanthamoeba motility and growth that could enhance its environmental prevalence, protecting Acanthamoeba from the pathogenic Legionella spp. and enhancing Acanthamoeba pathogenicity (reviewed in [55]). Using advanced molecular "omics" technologies, there is a need for a holistic approach to understand the microbial community dynamics in natural environments to comprehend effect/function of each symbiont and their prevalence in complex ecological populations.…”
Section: Monkeypox Virus Interaction With Its Hostsmentioning
confidence: 99%